Distortion-Based Link Adaptation for Wireless Video Transmission. (15th June 2008) - Ferré Ferré, Pierre Pierre; Chung-How Chung-How, James James; Bull Bull, David David; Nix Nix, Andrew Andrew
Abstract : Wireless local area networks (WLANs) such as IEEE 802.11a/g utilise numerous transmission modes, each providing different throughputs and reliability levels. Most link adaptation algorithms proposed in the literature (i) maximise the error-free data throughput, (ii) do not take into account the content of the data stream, and (iii) rely strongly on the use of ARQ. Low-latency applications, such as real-time video transmission, do not permit large numbers of retransmission. In this paper, a novel link adaptation scheme is presented that improves the quality of service (QoS) for video transmission. Rather than maximising the error-free throughput, our scheme minimises the video distortion of the received sequence. With the use of simple and local rate distortion measures and end-to-end distortion models at the video encoder, the proposed scheme estimates the received video distortion at the current transmission rate, as well as on the adjacent lower and higher rates. This allows the system to select the link-speed which offers the lowest distortion and to adapt to the channel conditions. Simulation results are presented using the MPEG-4/AVC H.264 video compression standard over IEEE 802.11g. The results show that the proposed system closely follows the optimum theoretic solution.